Music education for the 21st century: Epistemology and ontology as bases for student aesthetic education. - Aróstegui, José Luis; Stake, Robert; Simons, Helen (Education Policy Analysis Archives, 2004)
We seek to understand why persons develop their musical preferences by identifying with a particular cultural group and social background. This identification is greatly shaped by experience in their environment. Resources employed for this identification are mostly different from those employed in schools to foster academic knowledge. We argue that there needs to be renewed attention to the epistemological and ontological bases of education to examine how we can most effectively educate for the 21st Century in a relativistic and globalized world. Our focus is on music education but with the entire curriculum near at hand, together seeking to bring about a better intellectual, sociological, and aesthetic process of education. Our interest in music stems from a perceived necessity that persons trained in the arts will have special answers to the challenges of this so-called postmodern world. We offer: (1) elements of epistemology, discussing how education and music education have traditionally been focused on propositional rather than interpretive knowledge; (2) a particular perspective on ontology, making evident the ways that individuals construct meanings, interacting with their cultural environment in the shaping of social identity; and (3) the need, today more than ever, for a music curriculum fostering aesthetic experiences that develop interpretive understanding of reality and personal self. Characteristics of postmodernism in cultural studies will be employed throughout the paper.